(untitled) (Journal of Hama University, 2025)
This study aimed to measure the degree to which seventh grade students possess grammatical skills. To achieve the objectives of the study, a sample consisting of (50) students was selected. The researcher used the descriptive analytical method. The study tool, represented by a list of grammatical skills appropriate for the seventh grade, was used, in addition to an achievement test. The results of the study revealed that there was a general weakness among students in grammatical skills as a whole, as the percentage of their possession of grammatical skills reached (29%), in addition to students’ weakness in sub-grammatical skills, where the percentage ranged between (16%) and (34%), which is a low percentage In view of the research into many proposals, the most important of which are: conducting evaluation studies of grammatical skills in the Arabic language curriculum at the basic education stage, envisioning preparation for a unit that needs to develop students’ grammatical skills.